First report of fesavirus 4 detection from cats in Japan - Shwe Thiri MAUNG MAUNG KHIN; SHEIKHI, Mohammad Jafar; TAKEMAE, Hitoshi; MIZUTANI, Tetsuya; FURUYA, Tetsuya (Journal of Veterinary Medical Science, 2024)
Fesaviruses, picorna-like RNA viruses, were discovered in 2014 in feces from cats in an animal shelter in the United States but have not since been reported elsewhere. In this study, we collected cat fecal samples from 20 adult cats from an animal shelter in Tokyo, Japan, and examined them for viral pathogens. Next generation sequencing (NGS) was performed to detect both RNA and DNA virus sequences. Sequences of a total of 7 RNA viruses including some common feline pathogenic viruses were detected across 8 samples, while no DNA virus sequences were identified in any sample. Of the RNA virus sequences detected in the samples, two sequences, 4,746 and 4,439 bp, demonstrated 90.3% and 85.0% similarity, respectively, to the fesavirus 4 sequence in the database. To confirm the NGS results, quantitative RT-PCR (qRT-PCR) assays were developed using specific primers and probes designed based on the contig sequences. Based on the qRT-PCR assays, we detected relatively high copy-numbers of fesavirus 4 RNA in the two fecal samples from which the fesavirus 4 sequences were originally obtained, and low copy numbers in other samples. These results demonstrate the presence of fesavirus 4 in cats in Japan for the first time.